2011
DOI: 10.1111/j.1540-4781.2011.01272.x
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Corrective Feedback and Textual Enhancement in Promoting the Acquisition of Grammatical Redundancies

Abstract: advocated the use of negative feedback to promote learner noticing of errors and the internalization of correct forms. At the same time, the true efficacy of this practice is uncertain, for it not only entails additional linguistic input but may generally enhance otherwise non-salient language features as well (Leeman, 2003). This study examined the development of theà/au/en/aux distinction before French toponyms among 136 2nd-semester university French learners randomly assigned to an interactive, computer-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 37 publications
0
15
1
Order By: Relevance
“…From observing the teachers, it is clear that input enhancement has encouraged teachers to bring a stronger focus on the targeted forms. Research (Cho 2010;Lyddon 2011;Sharwood-Smith 1993;Winke 2013;Wong 2004) on input enhancement has shown that it also helps learners be more aware of the forms. However, this experiment does not sufficiently prove the efficacy of this particular method.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…From observing the teachers, it is clear that input enhancement has encouraged teachers to bring a stronger focus on the targeted forms. Research (Cho 2010;Lyddon 2011;Sharwood-Smith 1993;Winke 2013;Wong 2004) on input enhancement has shown that it also helps learners be more aware of the forms. However, this experiment does not sufficiently prove the efficacy of this particular method.…”
Section: Discussionmentioning
confidence: 97%
“…The material was Innovation in Language Learning and Teaching 225 identical for both groups, apart from the following exception: the highlighted lexical, grammatical and cultural features for the focus-on-form treatment group (the pronoun que was highlighted with green, bolded and underlined; the pronoun qui with red, bolded and underlined; lexical and cultural words were in purple, bolded and underlined). The primary motivations for this color enhancement are that the researcher hoped that it would remind teachers to focus on the different types of forms and that learners would have a better chance of noticing forms if the forms were enhanced (Cho 2010;Lyddon 2011;Sharwood-Smith 1993;Winke 2013;Wong 2004). As previously mentioned, Winke (2013) particularly points out that input enhancement is a good tool for bringing saliency to forms in an implicit manner and guide teachers in doing so.…”
Section: Target Structures and Treatment Designmentioning
confidence: 98%
See 1 more Smart Citation
“…3rd sg ‐ s in English is also grammatically redundant because the subject already indicates person and number. In a CF study focusing on grammatically redundant variants of à before French place names, Lyddon () found no differences between several different types of CF, indicating that grammatically redundant structures might be less sensitive to CF variation.…”
Section: Acquisition Of English Subject–verb Agreementmentioning
confidence: 99%
“…Lyddon (Lyddon, 2011) examines college students learning foreign (French) language and investigates how teachers react to students' mistakes. He examines which form of correction (the teacher's response to the students' errors) is the most effective.…”
Section: Empirical Investigations Of Redundancymentioning
confidence: 99%